SURVEY AND ANALYSIS OF INTERCULTURAL COMMUNICATION IN BULGARIA AND ABROAD - Andreeva, Gergana; Andreev, Andrey (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The membership of Bulgaria in NATO and the European Union brings new challenges and tasks to the Bulgarian Armed forces in the complex and dynamic security environment. The participation of military forces from the Bulgarian Army in international joint operations and missions led by NATO, the EU and the UN, transforms English language fluency into an important aspect of improving our operational interoperability with allies and partners. Teaching English is a priority for the modernization and transformation of the Bulgarian Army. The system of education in English does not exist in isolation and is influenced by a number of factors that affect the force as a whole. It is a process that spans a long period of time and does not give quick results. This feature poses one of the challenges facing the system of English language training for the introduction of new effective forms of communication. In this respect, it is topical to explore and analyze opportunities for the introduction of Intercultural Communication in language learning groups within the Bulgarian Ministry of Defense.